Do We Have a Discipline? The Great Aust Lit Debate (Journal of the Association for the Study of Australian Literature, 2013)
The article surveys discussion of the state of the Australian literature to conclude that it is in decline. It argues that this may bring the opportunity for Australian literature to become part of more broadly based disciplines than mere 'literariness'.